2022
DOI: 10.1111/sjop.12816
|View full text |Cite
|
Sign up to set email alerts
|

To vaccinate or not: The relationship between conscientiousness and individual attitudes toward vaccination in real‐life contexts

Abstract: Despite the availability of a safe and effective vaccine being well‐recognized as a critical tool to end the COVID‐19 pandemic, many individuals remain vaccine hesitant for various reasons. In the literature, one well‐established finding is that skeptical attitudes towards vaccination are higher amongst individuals low in conscientiousness. However, no research is available to corroborate whether the relationship between conscientiousness and intention to vaccinate has force in real life. The present research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…The higher scores of Vaxxers on Honesty/Humility and Conscientiousness align with recent findings on the topic (e.g., Li, 2022 ). They reflect the inclination of this group to be more aware of and to readily adhere to social norms and expectations, potentially combined with a heightened sense of responsibility towards the community.…”
Section: Discussionsupporting
confidence: 89%
“…The higher scores of Vaxxers on Honesty/Humility and Conscientiousness align with recent findings on the topic (e.g., Li, 2022 ). They reflect the inclination of this group to be more aware of and to readily adhere to social norms and expectations, potentially combined with a heightened sense of responsibility towards the community.…”
Section: Discussionsupporting
confidence: 89%
“…Conscientiousness, agreeableness, and openness showed positive links in some studies but virtually no associations in others (Gonçalves et al, 2022;Graeber et al, 2021;Mo et al, 2021). For instance, Li (2022) observed a positive relationship between conscientiousness and the willingness to get vaccinated against COVID-19, whereas other studies observed no significant correlation between these factors (Gonçalves et al, 2022;Graeber et al, 2021). For neuroticism, studies suggest no significant relationship with the willingness to get vaccinated against COVID-19 (Gonçalves et al, 2022, Howard, 2022.…”
Section: Big Five and Covid-19mentioning
confidence: 99%
“…The unsteady nature of the number of doses and COVID-19 vaccine efficacy as compared to other vaccines may inform conscientious people in their attitudes towards the COVID-19 vaccines. Other studies have expressed mixed findings regarding the role personality plays in vaccine hesitancy [33,34] indicating that there are inconsistent findings regarding personality and vaccine acceptance.…”
Section: Plos Global Public Healthmentioning
confidence: 99%